Lettran kit: Mathematics tool innovation for the rational numbers topic / Mohamad Faiz Farhan Abdul Rahman ... [et al.] - Abdul Rahman, Mohamad Faiz Farhan; Shafie, Sabarina; Zamzamir, Zamzana; Hasan, Norsida; Rahmat, Fainida (2024)
Let’s Treasure The Rational Numbers (LeTTRaN) Kit is a teaching aid that integrates the game-based learning (GBL) approach. The development of the LeTTRaN Kit was motivated by the findings of a need analysis study for the development of a mathematics kit that integrated the GBL approach. The design of the LeTTRaN Kit follows the five phases of the ADDIE model: analysis phase, design phase, development phase, implementation phase, and evaluation phase. LeTTRaN Kit is developed solidly to assist the teaching and learning process for mathematics subjects focusing on the Rational Numbers topic. There are five components representing the LeTTRaN Kit: the LeTTRaN application, instructional material, lesson plan, activity sheet and worksheet. All components have their functions and play a role in completing teaching and learning activities using the LeTTRaN Kit. Besides, the LeTTRaN Kit has successfully undergone evaluation, including validation and usability testing. According to expert validation findings, the LeTTRaN Kit obtained satisfactory validity for its face and content. Furthermore, after implementing the LeTTRaN Kit, the usability results showed a high mean score, indicating the high impact of using the LeTTRaN Kit in the teaching and learning process. Overall, the LeTTRaN Kit is validated as a good teaching aid in improving student achievement and motivation in the rational numbers topic. It can serve as a viable alternative for classroom instruction and guide teachers in creating teaching aids that integrate GBL.